Different β‐cell secretory phenotype in non‐obese compared to obese early type 2 diabetes. Issue 5 (17th February 2020) - Gudipaty, Lalitha; Rosenfeld, Nora K.; Fuller, Carissa S.; Cuchel, Marina; Rickels, Michael R.
Abstract: Background: Type 2 diabetes (T2D) is characterized by impaired tissue sensitivity to insulin action (ie, insulin resistance) and impaired β‐cell insulin secretion. Because obesity contributes importantly to the development of insulin resistance, we sought to determine whether insulin secretory defects would predominate in non‐obese compared to obese T2D. Methods: We measured β‐cell function and secretory capacity using the glucose‐potentiated arginine test in T2D subjects early in the disease course classified as non‐obese (BMI <30; n = 12) or obese (BMI ≥30 kg/m 2 ; n = 28) and additionally compared responses from non‐obese T2D with a non‐diabetic control group (n = 12). Results: The acute insulin response to glucose potentiation of arginine‐induced insulin release was less in non‐obese T2D than in controls and associated with impaired β‐cell sensitivity to glucose (PG50 ). Proinsulin secretory ratios were increased in non‐obese T2D when compared to obese T2D. Obese T2D subjects had reduced insulin sensitivity (M/I) while non‐obese T2D subjects had insulin sensitivity that was comparable to controls. Conclusions: In non‐obese T2D, insulin secretory defects predominate with impaired β‐cell sensitivity to glucose and proinsulin processing in the absence of insulin resistance. Future studies should consider whether different β‐cell secretory phenotypes and tissue sensitivity to insulin explain the varying responsiveness to T2D interventions.